Visualização da informação aplicada à estratégia competitiva de uma Instituição Educacional - Rauter, André; Benato, Karina (Revista Gestão da Produção Operações e Sistemas, 2006)
The Information Technology (IT), through Business Intelligence (BI), associated to the Competitive Intelligence(CI) administrative theory, support the decision makers in the search, access and analysis of the strategicinformation from various sources. This paper specifically deals with Information Visualization, an IT area intune with Business Intelligence concepts, applied to the graphic comparison of links from the pages ofcompetiting educational institutions. This technology provides the strategists with visual information so thatdecisions can be made. This research reinforces the theoretical and practical initiatives in the development ofstudies in the management area, associated with the Information Visualization, in the making of an IntelligentBusiness.Keywords: Decision-making process; Information visualization; Competitive intelligence; Business intelligence.